2021
DOI: 10.3390/antiox10030350
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Resistance Training on the Redox Status of Skeletal Muscle in Older Adults

Abstract: The aim of this study was to investigate the effects of resistance training (RT) on the redox status of skeletal muscle in older adults. Thirteen males aged 64 ± 9 years performed full-body RT 2x/week for 6 weeks. Muscle biopsies were obtained from the vastus lateralis prior to and following RT. The mRNA, protein, and enzymatic activity levels of various endogenous antioxidants were determined. In addition, skeletal muscle 4-hydroxynonenal and protein carbonyls were determined as markers of oxidative damage. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 50 publications
0
9
1
Order By: Relevance
“…Among the genes downregulated in the EVs from exercised rats were Gpx3 (glutathione peroxidase 3), Pxdn (peroxidasin) and Selenof (selenoprotein F) that are associated with the molecular function "oxidoreductase activity, acting on peroxide as acceptor"; two of them-Gpx3 and Selenof are also associated with "selenium binding". Although several studies have shown that the levels of oxidative stress markers such as glutathione peroxidase increase during the exercise (Khcharem et al, 2021;Mesquita et al, 2021), our results suggest that their baseline levels are lower in exercised than in sedentary animals. Among the DEGs were two miRNAs-miR378b and miR35, that were present in the runner EVs but undetectable in the sedentary rat EVs.…”
Section: Discussioncontrasting
confidence: 84%
“…Among the genes downregulated in the EVs from exercised rats were Gpx3 (glutathione peroxidase 3), Pxdn (peroxidasin) and Selenof (selenoprotein F) that are associated with the molecular function "oxidoreductase activity, acting on peroxide as acceptor"; two of them-Gpx3 and Selenof are also associated with "selenium binding". Although several studies have shown that the levels of oxidative stress markers such as glutathione peroxidase increase during the exercise (Khcharem et al, 2021;Mesquita et al, 2021), our results suggest that their baseline levels are lower in exercised than in sedentary animals. Among the DEGs were two miRNAs-miR378b and miR35, that were present in the runner EVs but undetectable in the sedentary rat EVs.…”
Section: Discussioncontrasting
confidence: 84%
“…This is an unfavorable condition that can lead to cell and tissue damage and plays a role in aging; inflammatory processes; the development, initiation, and progression of cardiovascular, neurodegenerative, and cancerous lesions [ 26 , 27 ]. The relationship between exercise and oxidative stress is extremely complex, depending on the type, intensity and length of the workout [ 28 , 29 ]. In addition to the many positive health effects of regular, moderate exercise, it also reduces oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…Our finding showed the reinforcing effect of exercise on supplement in the context of antioxidant capacity, but resistance training was more effective than supplementation alone. Consistent with this result, Mesquita et al stated that six weeks of resistance training increased total antioxidant capacity in older adults 59 . Another study by Amiri et al proved that 10 weeks of creatinine supplementation enhanced antioxidant capacity by inserting a synergistic effect on resistance training 60 .…”
Section: Discussionmentioning
confidence: 70%